PENGARUH PENGGUNAAN PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN WINGEOM TERHADAP KEMAMPUAN PEMECAHAN MASALAH GEOMETRI SISWA SMA - Ikhsanudin, Ikhsanudin (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
This research is a quasi-experimental with pre-test and post-test non-equivalent group design. The population in this research is all of the students on class X in SMA Negeri 1 Marga Tiga and the sampling technique is total sampling. Data are collected by documentation and test. Data are analyzed with descriptive statistics to compare the mean scores of N-GainÂ obtained by each student.Â The results of the analysis shows that (1) the studentâs geometry problem solving ability with cooperative learning STAD is higher than the conventional learning, (2) the studentâs geometry problem solving ability with wingeom software in cooperative learning STAD is higher than the conventional learning, (3) the studentâs geometry problem solving ability with wingeom software in cooperative learning STAD is higher than without using wingeom software. This research shows that the cooperative learning STAD by using the wingeom software has a significant effect on the high school studentsâ geometry problem-solving ability. The finding of this research shows that the students are still having difficulties in solving the problems, especially when the students have to look back whether the finishing is right or not.